2013
DOI: 10.1089/thy.2012.0332
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Transmission of Hypopituitarism: Critical Importance of Appropriate Interpretation of Thyroid Function Tests and Levothyroxine Therapy During Pregnancy

Abstract: Background: Typically, newborns with congenital hypothyroidism are asymptomatic at birth, having been exposed to euthyroid mothers. However, hypopituitarism may be associated with central hypothyroidism, preserved fertility, and autosomal dominant inheritance, requiring increased attention to thyroid management during pregnancy. Patient Findings: A woman with a history of growth hormone deficiency and central hypothyroidism gave birth to a term male neonate appropriate for gestational age. Due to low thyrotrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The POU1F1 missense p.R271W acts as a dominant inhibitor of transcription resulting in CPHD (142). A few p.R271W cases exhibit cognitive impairment or hearing impairment, which may be due to hypothyroidism during pregnancy when the mother carries the same variant (143). Approximately half of the p.R271W variants are fully penetrant.…”
Section: Pou1f1mentioning
confidence: 99%
“…The POU1F1 missense p.R271W acts as a dominant inhibitor of transcription resulting in CPHD (142). A few p.R271W cases exhibit cognitive impairment or hearing impairment, which may be due to hypothyroidism during pregnancy when the mother carries the same variant (143). Approximately half of the p.R271W variants are fully penetrant.…”
Section: Pou1f1mentioning
confidence: 99%
“…They may develop gestational hypothyroxinemia, which can be missed by routine TSH evaluation of the thyroid axis during pregnancy. This 'unnoticed' low T 4 in the mother can aggravate the hypothyroid state of the fetus who may well have inherited the genetic defect from the mother, overall resulting in short supplies of thyroid hormone to support normal fetal brain development, leading to severe CH with the consequences of gross motor and speech delay [90].…”
Section: Identification Etiological Investigations and Clinical Manamentioning
confidence: 99%
“…Women with hypothyroidism need increased thyroid hormone replacement to meet the increased demands of pregnancy. Failure to manage this properly can have lasting effects on the child’s hearing, which has been observed in the case of POU1F1 p.R271W mutation (Cuevas et al 2005; Haddow et al 1999; Lavado-Autric et al 2003; Pine-Twaddell et al 2013). Our study has identified candidate genes and pathways that could contribute to human variation in susceptibility to hypothyroidism-induced hearing impairment and neurological deficits.…”
Section: Discussionmentioning
confidence: 99%